The Effects of Magnetization Process on Methylene Blue Removal using Magnetically Modified Orange Peel - Munawer, Mohamad Huzair; Kiew, Peck Loo; Yeoh, Wei Ming (Progress in Energy and Environment, 2022)
Whilst adsorption process is the preferred method of purifying wastewater due to its benefits, problems with the recovery of spent adsorbents are still prevalent in wastewater treatment technology. The use of magnetized biomass-based adsorbents (biosorbents) to ease the regeneration process would be a novel approach to overcome this obstacle. The magnetization of orange peel adsorbent involves a series of preparation stages. In this context, there are several parameters that may affect the magnetization of orange peel (OP) such as the ratio between FeCl3•6H2O and FeCl2•4H2O, mass of untreated orange peel (UOP), volume of NH3 solution, magnetization temperature and magnetization period. In this study, Fractional Factorial Design (FFD) was adopted to identify the significant parameters affecting two different responses namely the success of magnetization process and methylene blue (MB) dye removal. Based on the ANoVA results, the significant parameters affecting the success of the magnetization process were magnetization temperature, interaction between ratio of FeCl2:FeCl3 and volume of ammonia, and mass of OP with duration of mixing. Whereas the significant parameters affecting the MB dye removal were all five of the individual parameters, along with the interaction of amount of OP with the other four parameters, interaction between volume of ammonia with duration of mixing and with ratio of FeCl2:FeCl3, interaction between duration of mixing with temperature and ratio of FeCl2:FeCl3, and interaction between temperature and ratio of FeCl2:FeCl3. The highest recorded MB removal was 89.18%, while the lowest recorded MB removal was 38.76%. The regeneration study also showed that magnetized orange peel could be regenerated at least six times without having a significant reduction in adsorption capacity. The major functional groups of magnetized orange peel before adsorption, after adsorption and after regeneration were all similar, indicating that the spent adsorbent could be regenerated.